The Effect of Tongue Twister Strategy on English Pronunciation and Fluency: A Literature Review - Costa, Yuliana Maria Da; Ratminingsih, Ni Made; Putra, I Nyoman Adi Jaya (Jurnal Locus Penelitian dan Pengabdian, 2025)
Good pronunciation and fluency competence are essential for effective communication in English, especially for second language (L2) learners, as it impacts message clarity, emotional expression, and speaker confidence. This article highlighted the importance of pronunciation and fluency competence in English language acquisition as well as the challenges faced by L2 learners and teachers. It emphasizes the need for differentiated and engaging learning methods, especially the use of tongue twister strategy, which have been shown to improve phonemic awareness, pronunciation ability, and fluency in a fun and interactive way. This article reviews several studies showing the effectiveness of tongue twister strategy in improving pronunciation and fluency competence, and increasing learners’ motivation. By integrating this strategy into language teaching, teachers can create a more effective and enjoyable learning environment, ultimately promoting better proficiency in English communication for their students.